A comprehensive perspective of traditional Arabic or Islamic medicinal plants as an adjuvant therapy against COVID-19 - Ahmed, Shabina Ishtiaq; Jamil, Sehrish; Ismatullah, Humaira; Hussain, Rashid; Bibi, Shabana; Khandaker, Mayeen Uddin *; Naveed, Aisha; Idris, Abubakr M.; Emran, Talha Bin (Elsevier, 2023)
COVID-19 is a pulmonary disease caused by SARS-CoV-2. More than 200 million individuals are infected by this globally. Pyrexia, coughing, shortness of breath, headaches, diarrhoea, sore throats, and body aches are among the typical symptoms of COVID-19. The virus enters into the host body by interacting with the ACE2 receptor. Despite many SARS-CoV-2 vaccines manufactured by distinct strategies but any evidence-based particular medication to combat COVID-19 is not available yet. However, further research is required to determine the safety and effectiveness profile of the present therapeutic approaches. In this study, we provide a summary of Traditional Arabic or Islamic medicinal (TAIM) plants’ historical use and their present role as adjuvant therapy for COVID-19. Herein, six medicinal plants Aloe barbadensis Miller, Olea europaea, Trigonella foenum-graecum, Nigella sativa, Cassia angustifolia, and Ficus carica have been studied based upon their pharmacological activities against viral infections. These plants include phytochemicals that have antiviral, immunomodulatory, antiasthmatic, antipyretic, and antitussive properties. These bioactive substances could be employed to control symptoms and enhance the development of a possible COVID-19 medicinal synthesis. To determine whether or if these TAIMs may be used as adjuvant therapy and are appropriate, a detailed evaluation is advised.